Effect of Media Interactive and Spatial Intelligence on Mathematics Learning Outcomes - Desi Nurillah; M. Syarif Sumantri; Sofia Hartati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to obtain an overview of interactive and interactive ppt learning media (external factors) and high and low spatial intelligence (internal factors) on mathematics teaching results in Malang Ibtidaiyah madrasah/ elementary school. The affordable population is the entire regular first graders of the 2021/2022 school year consisting of 5 parallel classes with 120 students. Sampling from the people is done randomly regardless of the strata present in the population. The determination of practical classes and control classes is done by drawn two categories drawn in the existing class's research. This study was conducted on first graders divided into two groups: the group of students given treatment and the group that served as control. The results of students' spatial intelligence instruments determine groups with high spatial intelligence and groups with low spatial intelligence. The study results show no difference in mathematics learning results towards students given the treatment of learning between video tutorials and interactive powerpoint text. While students who have exceptional low Intelligence and high Intelligence, there are differences in learning outcomes.